Lantatur Sebagai Alternatif Layanan Perpustakaan Sekolah di Masa Pandemi Covid-19 - Istiqomah, Zeni; Anjali, Muhammad Erdiansyah Cholid (Daluang: Journal of Library and Information Science, 2021)
Background: Library services must continue in the conditions of the Covid-19 pandemic and learning is carried out online. SMA Muhammadiyah 1 (Muhi) Yogyakarta Library has innovations in providing services, so that its role is not replaced by other service providers. One of them is by implementing the service without going down (drive thru). The purpose of this study is to analyze the determination of the drive thru service system in the library of SMA Muhi Yogyakarta during the pandemic and to analyze the obstacles experienced.Methods: This study uses a qualitative approach with descriptive methods. Data were collected through observation, interviews, and documentation study. The data validity test was carried out by using the source triangulation test and data analysis was carried out by data reduction, data presentation, and drawing conclusions.Results: The results show that the implementation of the drive thru service system has been carried out since July 2020. The drive thru service is implemented through two mechanisms, namely scheduled and unscheduled. The scheduled drive thru service implementation mechanism is adjusted to the implementation time agreed upon by the library, school leaders, and library users. Meanwhile, the implementation of unscheduled drive thru services is more flexible according to the agreement between the librarian and the user.Conclusion: Each drive thru system has grooves and procedures, making it easier for the user. The obstacles faced in this service lie in the infrastructure provided, limited human resources, and regulations for the implementation of the drive thru service.